Mars beckons : the mysteries, the challenges, the expectations of our next great adventure in space - Wilford, John Noble (New York : Knopf, 1990)
Discusses our fascination with the planet through the ages and our designs on the planet as a future site of exploration.
The allure of another world -- Lowell's Mars -- The Martians are coming! -- First encounters -- The moons of Mars -- Viking and the search for life -- An inventory of knowledge--and questions -- The Russians are going -- American indecision -- Together to Mars -- Destiny.
Includes bibliographical references (p. 224-232) and index.
Young Adult.
Keywords: Life on other planets; Life on other planets; Mars (Planet); Mars (Planet) -- Exploration; Mars (Planet); Mars (Planet) -- Exploration